DNA Barcoding : Current Advances and Future Prospects -A Review - Vohra, Prerna; Khera, K.S (Asian Journal of Biological and Life Sciences, 2013)
DNAbarcoding is a molecular-based identification system, recently introduced in the scientific community. This method is not new to science, but the real innovation is not in the discrimination system itself. DNA barcoding can be considered as the core of an integrated taxonomic system. It is established that the mitochondrial gene cytochrome c oxidase I (COI) can serve as the core of a global bioidentification system for animals. Now days, this approach has become increasingly popular and advances as well as limitations have clearly emerged as increasing amounts of organisms have been studied.